Analysis of Perigee-Apogee Longitude Classification with Crescent Visibility Years 1300H-1600H Based on New MABIMS Criteria - Puput Dwi Aryani; Novi Sopwan; Ahmad Syifaul Anam (Universitas Islam Negeri Mataram, 2026)
The determination of the beginning of the Hijri month in Indonesia still faces inconsistencies due to the complexity of astronomical parameters. This study analyzes the classification pattern of the Moon's perigee-apogee longitude position in relation to the visibility level of the crescent moon during the 1300H-1600H period to provide an in depth understanding of the orbital factors in determining the beginning of the Hijri month in Indonesia. A descriptive quantitative method was used by analyzing 10,836 data from three locations (Sabang, Surabaya, and Merauke) using astronomical algorithms from Chapront-Touze & Jean Meeus based on the New MABIMS and Odeh criteria. The results show that crescent visibility frequency at the apogee position is higher than at perigee under both criteria, with New MABIMS recording 1,314 apogee compared to 163 perigee cases, and Odeh recording 1,113 apogee compared to 127 perigee cases. New MABIMS consistently yielded higher overall visibility rates (4,539 cases) than Odeh (2,353 cases), a difference statistically confirmed through a chi-square test of independence across all three cities (p<0.001). The data distribution pattern is relatively consistent across the three locations, with orbital factors proving more dominant than geographical factors in determining crescent visibility. This study provides an initial overview that the Moon's orbital dynamics have the potential to provide additional context in crescent observations. Empirical validation through actual observation data and the integration of atmospheric factors are needed to produce a more comprehensive and applicable understanding.